Mechanical and Thermal Properties of Polymer Blends Composites Reinforced with Nano Filler - Rafah Alwan Nassif; Raghad Hamid Hilal (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
This study aims to enhance the mechanical and thermal properties of polymer blends (HDPE and PP) by incorporating nanofillers, including carbon nanotubes (CNTs), graphene oxide (GO), and silica nanoparticles (SiO₂). The effects of nanofiller concentrations (1%, 2%, and 3% by weight) on tensile, impact, and flexural strengths, and thermal stability were investigated. The results showed that adding 2% CNTs increased tensile strength by 50% compared to the unmodified blend. Impact and flexural strengths also improved significantly with the addition of CNTs, while the improvements were less pronounced with GO and SiO₂. Thermal stability was enhanced by all nanofillers, with the CNT and GO composites showing a 25% increase in decomposition temperature compared to the unmodified blend. X-ray diffraction analysis revealed that nanofillers increased the crystallinity of the blends, thereby improving strength and stability. These findings suggest that CNTs, GO, and SiO₂ significantly enhance the mechanical and thermal properties of polymer blends, making them suitable for applications in industries such as automotive, aerospace, and electronics.